Characteristics and Rhodamine B Adsorption Ability of Modified Sepiolites - Thao, Nguyen Tien; Huyen, Ta Thi; Ly, Doan Thi Huong; Nga, Han Thi Phuong (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: